RUSSIAN AVANT-GARDE MUSIC OF THE EARLY 20TH CENTURY IN THE MODERN CULTURE - O. A. Lyzlova (Концепт: философия, религия, культура, 2017)
Avant-garde became a global cultural phenomenon of the 20th century, essentially symbolizing the epoch. It’s impossible to picture the 20th century image without avant-garde. Nevertheless, the study of the Russian first wave musical avant-garde is still challenging since this unique phenomenon was neglected by national science on ideological grounds. In this article the author discusses the dual character of avant-garde, its ability to resist tradition, interacting with it at the same time and creating conditions for the synthesis of new, interesting and promising forms. The article presents key personalities of the Russian first wave musical avant-garde, such as: N. Kulbin, actually elaborating theoretical foundation of the Russian avant-garde music reflected in his article “Free music”; I. Vyshnegradsky, following N. Kulbin and proceeding to investigate theoretically the technique of quarter tones as well as to use it for music and new instruments’ creation. The paper also focuses on those composers who followed their own independent way inventing original systems of sound organization, among them: A. Avraamov, who invented a musical system with the octave divided into 48 equal intervals; N. Obukhov who developed the concept of 12-tone atonal techniques apart from A. Schoenberg. The author examines the main theoretical ideas of the musical avant-garde and their practical implementations, presents historical parallels with current musical trends, and analyzes the reasons for the Russian musical avant-garde short life and its significance for world music.